Women and the Local: Promotion or New Confinement in African Cities? - (:unkn) unknown (My University, 2011)
This paper examines the way in which women and the local scale are being jointly promoted in development policies, and what this entails politically. Models of participation and citizenship that strive for greater justice may well procude new spatial injustices by confininf women at particular scales and within particular actions. Drawing on research in Subsaharan Africa, the paper delves further into the way « projects » operate in planning and city management. It looks in greater detail at policy-making and how it interfere with different paths to construct local political spaces.
Keywords: African Research